2022
DOI: 10.1259/dmfr.20220113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the compatibility of C2, C3, and C4 fractal dimension values with hand-wrist and cervical vertebra maturation methods in determining skeletal maturation

Abstract: Objectives: To examine the correlation between the fractal dimension (FD) values of cervical vertebrae (C2, C3, and C4) and hand-wrist maturation (HWM) and cervical vertebra maturation (CVM) methods. In addition, the correlation between the pubertal growth spurt (PGS) and FD values was examined. Methods: The lateral cephalometric and hand-wrist radiographs of 120 subjects (61 females and 59 males) aged 8–18 years with a mean age of 13 years, were evaluated retrospectively. The CVM stages were determined in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
5
1
Order By: Relevance
“…In addition, a moderate correlation was found between C3 and C4 FD values. As opposed to the current study, no statistically significant correlations were found between FD values of the cervical vertebrae (C2, C3, C4) and chronological age, HWMS or CVMS in a study by Pamukçu et al investigating the correlation of FD measurements from the cervical vertebrae with HWMS and CVMS on radiographs of 120 subjects [ 13 ]. However, again in contrast to the current study, when HWMS and CVMS were divided into two groups according to pubertal growth spurt (PGS) as pre-PGS and post-PGS, significant negative correlations were found between C4 FD values and HWMS or CVMS both in females and in the entire sample in the same study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, a moderate correlation was found between C3 and C4 FD values. As opposed to the current study, no statistically significant correlations were found between FD values of the cervical vertebrae (C2, C3, C4) and chronological age, HWMS or CVMS in a study by Pamukçu et al investigating the correlation of FD measurements from the cervical vertebrae with HWMS and CVMS on radiographs of 120 subjects [ 13 ]. However, again in contrast to the current study, when HWMS and CVMS were divided into two groups according to pubertal growth spurt (PGS) as pre-PGS and post-PGS, significant negative correlations were found between C4 FD values and HWMS or CVMS both in females and in the entire sample in the same study.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on this finding, the authors suggested that the C4 FD value can be used as an objective tool to predict skeletal maturation stage and especially pubertal growth spurt. The limited sample size, the absence of testing for intra-observer agreement and uneven distributions of sex and patients among the stages may have accounted for the different results reported by Pamukçu et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females are more advanced than males in skeletal maturation. The growth spurt of female adolescents commenced four months earlier and extended for an additional four months compared to males [ 26 ]. A disparity between chronological age and skeletal maturity arises, particularly among females, at puberty initiation owing to the secretion of gonadotropin-releasing (GnRH) and sex hormones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%